Design of the composite hydraulic cylinder with geodesic dome trajectory: A numerical study. Issue 9 (20th August 2022) - Coskun, Taner; Sahin, Omer Sinan
Abstract: Hydraulic cylinders are used in many different areas from aviation to construction machinery and are generally manufactured using conventional steels that stand out with their low strength to weight ratio. In this study, it was aimed to design a hydraulic cylinder using composite materials to reduce cylinder weight. In this context, a novel composite hydraulic cylinder was designed, and numerical analyses for the composite portions of the hydraulic cylinder were carried out. For the numerical model, an aluminium liner and cylinder heads with the geodesic dome profiles were used, and composite layers were formed on their surfaces by using the Ansys ACP module. In the numerical analyses, the design parameters such as fabric materials and liner thickness were optimized using response surface optimization, and thus the optimum design parameters were determined. The results were verified by comparing the statistical‐based optimization and numerical analysis results. On the other hand, the wall thickness for the steel hydraulic cylinder, which has the same strength as the composite cylinder, was determined and the structure weights have been compared. As a result of the current study, it has been revealed that composite hydraulic cylinders with the same strength as steel hydraulic cylinders can be designed. With the utilization of the composite materials, it has been observed that composite hydraulic cylinder is 53.78% lighter than conventional hydraulic cylinders. Furthermore, the advantages and disadvantages of the novel composite hydraulic cylinder were discussed, and it was found to be feasible for industrial applications in which system weights are the major problem. Abstract :